2003
DOI: 10.1152/jn.00111.2003
|View full text |Cite
|
Sign up to set email alerts
|

Response Transformation and Receptive-Field Synthesis in the Lemniscal Trigeminothalamic Circuit

Abstract: To understand how the lemniscal trigeminothalamic circuit (PrV --> VPM) of the rodent whisker-to-barrel pathway transforms afferent signals, we applied ramp-and-hold deflections to individual whiskers of lightly narcotized rats while recording the extracellular responses of neurons in either the ventroposterior medial (VPM) thalamic nucleus or in brain stem nucleus principalis (PrV). In PrV, only those neurons antidromically determined to project to VPM were selected for recording. We found that VPM neurons ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…2 A) (Simons and Carvell, 1989;Minnery et al, 2003). The mean tuning ratio, defined as the average ON response (all angles) divided by the ON response at the best angle was 0.54 Ϯ 0.10, indicating a maximum angle ON response that was approximately double that of the average ON response.…”
Section: Resultsmentioning
confidence: 99%
“…2 A) (Simons and Carvell, 1989;Minnery et al, 2003). The mean tuning ratio, defined as the average ON response (all angles) divided by the ON response at the best angle was 0.54 Ϯ 0.10, indicating a maximum angle ON response that was approximately double that of the average ON response.…”
Section: Resultsmentioning
confidence: 99%
“…Posterior nucleus neurons respond weakly and with long (Ͼ20 ms) latencies to whisker deflections under anesthesia (Diamond et al 1992a;Lavallee et al 2005), so their activity is unlikely to contribute to the responses we observed. Early studies emphasized that RFs in VPM were dominated by the PW (Waite 1973b;Shosaku 1985;Rhoades et al 1987;Sumitomo and Iwama 1987;Chiaia et al 1991), but there is extensive evidence that many VPM neurons have multiwhisker RFs, particularly under light anesthesia (Waite 1973a;Simons and Carvell 1989;Armstrong-James and Callahan 1991;Lee et al 1994a,b;Bruno and Simons 2002;Minnery et al 2003;Timofeeva et al 2004;Aguilar and Castro-Alamancos 2005). Thorough mapping of VPM RFs in awake animals or those under light anesthesia yields large mean RF sizes and maximal RFs of 10 or more whiskers, consistent with our findings (Ito 1988;Diamond et al 1992a;Nicolelis et al 1993;Nicolelis and Chapin 1994;Friedberg et al 1999Friedberg et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the rat have shown that neurons in a single whisker-specific unit in the VPm (barreloid) have different angular preferences to whisker motion, although they all receive inputs from the same whisker (Brecht and Sakmann, 2002;Temereanca and Simons, 2003;Timofeeva et al, 2003). This angular preference is likely to arise from selective innervation by directional sensitive neurons in the Pr5 (Minnery et al, 2003). The remodeling process at VPm relay synapses may play a key role in establishing angular selectivity of VPm neurons within the same barreloid.…”
Section: Experience-dependent Synaptic Refinement At Vpm Relay Synapsementioning
confidence: 98%